Desenvolvimento de um processo de medição dimensional para placas cerâmicas de grande formato - Silva, Fernando das Dores (Universidade Federal de São Carlos, 2023)
In the Brazilian ceramic tile market, large-format ceramic tiles have gained prominence. In 2019, the country ranked as the third-largest global producer, second in consumption, and seventh in exports. The growth in large-format tile production is a result of technological advancements in conformation, enabling the creation of larger and more diverse formats. Despite technological advances in ceramic tile production, the dimensional measurement method (ISO 10545-2) has remained unchanged since the 1990s, becoming unsuitable for the high-quality and precision requirements of modern tiles. To address this gap, this dissertation proposed a Coordinate Measurement System (CMS) that measures the tile at an 83° incline as an alternative to the Current Measurement System (CuMS). The main objective of the research was to develop a testing methodology that would allow for the measurement of the dimensional characteristics of large-format ceramic tiles with repeatability and reproducibility (R&R) compatible with the current method and eliminating planar deformation. The results indicated that several variables, such as format, thickness, and typology of the tiles, affect elastic deformation. The format showed a variation of up to 1.42 mm in the largest dimension, thickness varied by 0.8 mm in thin tiles, and typology influenced by 0.77 mm in BIIb. Furthermore, a significant interaction was observed between these variables, especially in larger sizes. In the method development process, the Three-Dimensional Measurement Arm (TMA) was chosen due to its cost-effectiveness. The developed program allowed for measurements to be replicated without the need for manual rotation of the tiles, and the inclined panel with a robust structure and support pins eliminated elastic deformation. The R&R results between the CuMS and the CMS demonstrated average amplitude ranging from 0.013 mm to 0.075 mm, with standard deviations ranging from 0.062 mm to 0.114 mm, all below the resolution required by the standard.For specific tile attributes, such as size and lateral straightness, the results were 22% and 24% better than the specified limit of 30%. Deviations in characteristics such as orthogonality, warpage, central and lateral curvature also remained below the 20% limit, with values of 17%, 16%, 9%, and 14%, respectively. The repeatability of the characteristics ranged from 7% to 9%, below 10%, and no systematic deviations from stability and trend were observed in the SMC, while the CuMS exhibited some insignificant trend deviations. These results highlight the compatibility of the measurement systems and their ability to provide precise and standards-compliant measurements, ensuring effective control of dimensional variations. The results indicate that CMS is a viable alternative to CuMS for accurately measuring the dimensional characteristics of large-format ceramic tiles in compliance with standards. Thus, both methods together meet market demands for different sizes of ceramic tiles and ensure effective control of dimensional variations. It is worth noting that these methods can be used in conjunction, with CuMS suitable for pieces up to 60 cm in length, and CMS can be used for smaller pieces, but in terms of cost-effectiveness, it is recommended for larger sizes.
Development of a dimensional measurement process for large format ceramic tiles
Keywords: Placas cerâmicas; Análise de sistema de medição (MSA); Repetitividade e reprodutibilidade (R&R); Medição por coordenadas; Controle de qualidade; Ceramic tiles; Measurement system analysis (MSA); Repeatability and reproducibility (R&R); Coordinate measurement; Quality control; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO